2012
DOI: 10.3847/aer2009067
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Attitudes about Learning Science and Student Scientific Reasoning Skills

Abstract: Student attitudes about learning science and student ideas about the nature of science were compared at the end of two astronomy courses taught in Fall 2007, a course with a traditional astronomy curriculum and a transformed course, whose traditional astronomy curriculum was supplemented by an embedded curriculum that explicitly addressed the nature of science and student metacognition (i.e., thinking about one's own thinking.) The embedded curriculum in the transformed course gave students practice at evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The EBAPS suffers from a distinct lack of validity studies within literature, as others have also noted, despite its prominence as one of the more well-known epistemic instruments within physics education research [3][4][5][6][7]. It is important that instruments as influential as the EBAPS experience multiple validation studies so as to further establish the legitimacy of what the instrument claims to assess [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The EBAPS suffers from a distinct lack of validity studies within literature, as others have also noted, despite its prominence as one of the more well-known epistemic instruments within physics education research [3][4][5][6][7]. It is important that instruments as influential as the EBAPS experience multiple validation studies so as to further establish the legitimacy of what the instrument claims to assess [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, whereas teachers’ objectives used to be relatively constrained to helping students master course content, it is not uncommon for teachers’ goals to now also involve some combination of increasing students’ academic self-efficacy (Caprara et al . 2011; Marsh and Martin 2011), improving their self-regulatory capability (Boekaerts 2002; Zimmerman and Schunk 2011), enhancing their feelings toward learning (Duncan and Arthurs 2012), and instilling in them values and skills that promote lifelong learning (Aspin et al . 2012).…”
mentioning
confidence: 99%
“…Research into student epistemologies and scientific literacy has shown that non-science majors who take general education science courses have degraded attitudes toward science upon completion of these courses. [7][8][9] (We note that these authors use the term "attitudes" while we prefer the more accurate "epistemologies.") Exit interviews and final exam questions in these studies revealed that many students also leave these courses concerned that the ability to learn science is an innate trait that cannot be honed.…”
Section: Background and Overviewmentioning
confidence: 99%